2005
DOI: 10.1016/j.gca.2004.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Early diagenesis of carbohydrates and lignin in mangrove sediments subject to variable redox conditions (French Guiana)

Abstract: A comparative study of lignin and neutral carbohydrate compositions, combined with C, N and ␦ 13 C analyses, was carried out on sedimentary cores, and on various vascular plant species collected in mangrove swamps of French Guiana. The main purpose of this study was to assess the diagenesis of carbohydrates and lignin in brackish to hypersaline fine-grained mangrove sediments characterized by great changes in redox conditions. Distribution of carbohydrates in sediments reflects both the lability of these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
82
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 53 publications
8
82
1
5
Order By: Relevance
“…C values of the leaves of the two studied mangrove species and Salicornia are consistent with those found in the literature [36,37]. TOC, C/S, HI and OI measured in sediment cores of the different stands are displayed in Figure 4.…”
supporting
confidence: 89%
“…C values of the leaves of the two studied mangrove species and Salicornia are consistent with those found in the literature [36,37]. TOC, C/S, HI and OI measured in sediment cores of the different stands are displayed in Figure 4.…”
supporting
confidence: 89%
“…To our knowledge, although studies have looked at carbohydrate composition of temperate shallow sediments (Liebezeit 1987;Khodse et al 2008) and diagenesis in tropical intertidal muds (Marchand et al 2005), this is the first to examine the composition, production, and loss of carbohydrates in shallow subtidal sands in the subtropics. Furthermore, this is the first application of a HPLC-IRMS technique (Boschker et al 2008) to monitor carbon transfer to and from carbohydrates in a long-term (30 d) in situ 13 Clabeling experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate composition and concentration can be further affected by nutrient availability (Underwood et al 2004;Cook et al 2007) and environmental conditions (e.g., light and salinity) that influence growth of carbohydrate sources (e.g., algae; Smith and Underwood 2000;Perkins et al 2001;Abdullahi et al 2006). Because of the competing influences on carbohydrate composition, spectra are best interpreted in combination with additional sediment characteristics such as C : N ratios (Khodse et al 2008) and natural abundance stable isotope ratios (Marchand et al 2005).…”
mentioning
confidence: 99%
“…Studies using a combination of these bulk properties with molecular biomarker techniques (as the present study adopted) have been limited however. Boschker et al (1995) apply such methodologies in Lake Gooimer, and Marchand et al (2005) apply a similar approach to study the sediment in a mangrove system. Relatively comprehensive studies using multiple markers are reported in the Amazon system (Bernardes et al, 2004;Hedges et al, 1994).…”
mentioning
confidence: 99%